Bioprospection of volatile constituents of species of the genus Croton l. from the Delta do Parnaíba (Research, Society and Development, 2022)
The present study aimed to promote the bioprospecting of volatile constituents of species of the genus Croton L., as well as to evaluate the socio-economic potential allied to the biological activities of volatile constituents of these species present in the flora of the Delta do Parnaíba. To obtain the essential oils, samples of the aerial parts of Croton blanchetianus, C. campestris, C. floribundus, C. heliotropiifolius and C. rhamnifolius were collected and individually submitted to hydrodistillation and then analyzed by gas chromatography coupled to mass spectrometry (GC/MS) and coupled to a flame ionization detector (GC/FID). Identification of the volatile constituents was carried out by determining the simulated Kovats index and comparison with literature data. The essential oil of C. rhamnifolius was submitted to antimicrobial sensitivity test by the disk diffusion method. The phytochemical analysis identified 33 constituents in the essential oil of the five species, mainly monoterpenes (sabinene, limonene, α-pinene, p-cymene, eucalyptol) and sesquiterpenes (bicyclogermacrene, germacrene-D, trans-caryophyllene) very often as major constituents, which enabled the use of these compounds as chemical markers for taxonomic classification of species of the genus Croton. The sensitivity test to antimicrobials by the disk diffusion method showed promising inhibitory activity of C. rhamnifolius oil against Gram-negative strains of microorganisms, which makes this oil of great medicinal interest.